Bright stars, red giants, and white dwarfs - Berger, Melvin (New York : G.P. Putnam's Sons, 1983)
Describes the various stages in the birth, life, and death of stars and discusses theories about the ultimate future of our universe.
Includes index.
Booklist.
6.5
6.5
5-8.
5-8
Keywords: Astronomy -- Juvenile literature; Stars -- Juvenile literature; Astronomy; Stars; Astronomy; Stars